2005
DOI: 10.2134/agronj2005.0533
|View full text |Cite
|
Sign up to set email alerts
|

Topography and Management of Nitrogen and Fungicide Affects Diseases and Productivity of Canola

Abstract: undulating landscape, yield of wheat was reported to be greater on the upper SL when precipitation was above Successful application of precision agriculture technology requires average and greater on the lower SL when precipitation information on crop response to many factors including fertilization and disease management. Field experiments were conducted on a was below average (Manning et al., 2001c). Reduced hummocky landscape in the northern prairies to determine effects of crop yields on the lower SLs or s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
23
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 33 publications
14
23
1
Order By: Relevance
“…The increase in seed N content of linseed with the application of N and S could be due to the fact that N is an integral part of protein and the protein of linseed involves S containing amino acids like methionine and cystine. The increase in seed N content attained observed in the present study was in agreement with the findings of Dubey et al (1995) and Kutcher et al (2005) who reported that seed N content of canola increased significantly with increasing N rates. However, the combined effect of S and nitrogen application was inconsistent on seed and straw N contents.…”
Section: Seed and Straw Nitrogen Contentsupporting
confidence: 93%
“…The increase in seed N content of linseed with the application of N and S could be due to the fact that N is an integral part of protein and the protein of linseed involves S containing amino acids like methionine and cystine. The increase in seed N content attained observed in the present study was in agreement with the findings of Dubey et al (1995) and Kutcher et al (2005) who reported that seed N content of canola increased significantly with increasing N rates. However, the combined effect of S and nitrogen application was inconsistent on seed and straw N contents.…”
Section: Seed and Straw Nitrogen Contentsupporting
confidence: 93%
“…Likewise, Rathke et al(2005) linked this fact with reduced availability of carbohydrates for oil synthesis at high N application. The decrease in oil content of canola with the increasing levels of N is consistent with other reports (Jackson, 2000;Kutcher et al, 2005;Rathke et al, 2005;Cheema et al, 2001). The increase in oil content with the application of S favors the views of Marschner (1986) who stated that S is involved in the synthesis of oil.…”
Section: Oil Contentsupporting
confidence: 90%
“…Several reasons have been given by different researchers for the decrease in oil content with increasing N rates. For example, Kutcher et al(2005) stated that it might be due to the dilution effect of increased seed yield with increased N fertilization and the inverse relationship of protein and oil content. Jackson (2000) believed that N delays plant maturity which results in poor seed filling and greater proportion of green seed.…”
Section: Oil Contentmentioning
confidence: 99%
“…Differences of this magnitude were considered not to have agronomic importance. Maturity was later for the HYB than OP cultivar and did tend to be later as fertilizer rate increased, but the differences averaged less than 1 d. Other researchers in Saskatchewan have observed greater delays in maturity of canola with increasing rate of N fertilizer (Karamanos et al 2005;Kutcher et al 2005a). As seeding rate increased, days to maturity decreased and averaged 1.6 d earlier for the highest compared with the lowest seeding rate.…”
Section: Growing Periodmentioning
confidence: 78%
“…Cultivar and seeding rate effects on green seed were not consistent across location years, but similar fertilizer effects were noted at 5 of 8 site-years, and had no effect at the 3 remaining site-years. Others have reported increased proportion of green seeds in canola because of delayed maturity due to high N fertilization (Grant and Bailey 1993;Kutcher et al 2005a). Grant and Bailey (1993) reported that under low plant available soil N conditions application of N fertilizer usually increased protein concentration of canola seed but decreased oil concentration.…”
Section: Grain Qualitymentioning
confidence: 99%